Pengaruh whistleblowing system, kompetensi aparatur dan kesadaran Anti kecurangan terhadap pencegahan kecurangan (Studi Empiris Pada OPD Kota Pekanbaru Provinsi Riau) - Mardani Lista Arpani; Alfiati Silfi; Lila Anggraini (SYNERGY: Jurnal Bisnis dan Manajemen, 2022)
The purpose of this study was to determine the effect of the whistleblowing system, apparatus competence and anti-fraud awareness on fraud prevention studies at OPD Pekanbaru City, Riau Province. The population in this study were 43 Regional Apparatus Organizations (OPD) Pekanbaru City, Riau Province. Sampling using purposive sampling method with a total of 96 respondents. The data analysis technique is multiple linear regression. Based on the results of the study, it was concluded that the whistleblowing system, apparatus competence and anti-fraud awareness simultaneously and partially affected the prevention of fraud in OPD Pekanbaru City, Riau Province. The contribution of this influence is 50.4% while the remaining 49.6% is influenced by other variables not included in this study..